Pengaruh Pemangkasan Cabang Lateral dan Dosis Pemberian Pupuk NPK pada Tanaman Bunga Kol (Brassica Oleracea Var. Botrytis L) - Endang Suprapti; Agus Budiyono; Tyas Soemarah Kurnia Dewi; Daryanti; Alif Amirul Fatkhurahman (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2023)
Cauliflower is a vegetable that has commercial value and good prospects, especially for public consumption. According to the Central Bureau of Statistics of the Republic of Indonesia cauliflower production has decreased from 2019 to 2021, it is necessary to improve maintenance, one of which is by pruning lateral branches to increase productivity, thereby increasing the rate of photosynthesis to produce high productivity and the right dose of NPK fertilizer to maximize growth in the vegetative and generative phases thereby increasing the yield of cauliflower plants. This study aims to determine the effect of pruning lateral branches and doses of NPK fertilizer on the growth and yield of cauliflower. The research was conducted in the hamlet of Jinarum, Girilayu, Matesih, Karanganyar from July to September 2022. The research method used a Completely Randomized Block Design (RAKL) consisting of 2 treatment factors and 3 replications. The first factor is lateral branch pruning P0: without pruning, P1: pruning lateral branches 3 WAP, P2: pruning lateral branches 5 MST. The second factor is the dose of NPK fertilizer with doses of N1: 150 kg/ha, N2: 200 kg/ha, N3: 250 kg/ha. The results showed (1) Pruning lateral branches had a very significant effect on fresh stover, dry stover, crop diameter, crop weight per plant, and crop weight per plot. However, it did not have a significant effect on plant height and number of leaves. (2) NPK fertilizer doses had a very significant effect on fresh stover, dry stover, crop diameter, and crop weight per plant, had a significant effect on crop weight per plot, and had no significant effect on plant height and number of leaves. (3) The interaction between treatments had a very significant effect on fresh stover, dry stover, and crop weight per plant, and had no significant effect on plant height, number of leaves, crop diameter, and crop weight per plot. (4) The highest yield was obtained in the pruning treatment 3 weeks after planting with a dose of NPK fertilizer of 200 kg/ha, namely the crop weight of 11,997.4 grams per plot (. 26,644 kg/ha). Kata kunci : pruning lateral branches, the dose of NPK fertilizer